HIV-associated Hodgkin lymphoma at Groote Schuur Hospital, Western Cape, South Africa - Swart, Luhan (Division of Clinical Haematology, 2018)
Background: Human immunodeficiency virus (HIV) is associated with an increased risk of developing Hodgkin lymphoma (HL). South Africa (SA) has the highest HIV prevalence rate in the world. There is currently no 5-year overall survival (OS) outcome based data for HIV-associated HL from SA. Methods: A bone marrow database was compiled of all bone marrow biopsies (BMB) reported at National Health Laboratory Service (NHLS) Groote Schuur Hospital (GSH) between January 2005 and December 2012. Patients who had a BMB performed for staging of HL or where HL was diagnosed on the BMB were included for further analysis. Clinical and laboratory data was extracted from medical and laboratory records. Primary outcome measures included histological subtype, bone marrow infiltration (BMI) by HL, CD4 count, HIV-viral load (HIV-VL), tuberculosis (TB) data, treatment with chemotherapy and 5-year overall survival (OS). Results: The database included 6569 BMB and 219 patients of these had HL and were included for analysis. The median age at presentation (32 years) was similar in the HIV+ and HIV-populations. While males predominated in the HIV-group, females predominated in the HIV+ group (male:female ratio of 1.5:1 vs 0.7:1, respectively). The majority of patients (71%) were HIV negative (HIV-) and 29% were HIV positive (HIV+). The diagnosis of HL was made on BMB in 17% of cases. BMI was seen in 37%(82/219) overall, and was found in more HIV+ patients (61%; 39/64) than HIV-patients (28%; 43/155; p= 0.03). The histological subtype varied according to HIV status with nodular sclerosis classical Hodgkin lymphoma (NSCHL) being most frequent in the HIV-group and classical Hodgkin lymphoma (CHL)-unclassifiable the most frequent in the HIV+ group. HIV+ patients had a median CD4 count of 149 x106/L and 39% were anti-retroviral therapy (cART) naive at HL diagnosis. HIV+ patients had received anti-TB therapy more frequently than HIV-patients (72% vs 17%; p= 0.007). More HIV+ patients did not receive chemotherapy than HIV-patients (31% vs 3%; p= 0.001). The 5-year OS was 56%. HIV+ patients with BMI had a 5-year OS of 18%. BMI, HIV status, low CD4 count, histological subtype and TB therapy had a statistical significant impact on 5-year OS (p< 0.01). Conclusion: BMB provided the diagnosis of HL in 17% of cases, confirming its diagnostic utility in our setting. BMI by HL was more common in HIV+ patients and was associated with significantly worse survival. Our cohort showed similar survival outcomes to other countries in Africa, Asia and Central America with comparable socio-economic constraints to SA.